Implementation of Thematic Textbook Products Based on Augmented Reality - Haryati, Yuli; Kurniasih, Eem; Ismartoyo (Jurnal Smart Paud, 2024)
Learning about the theme of self in kindergarten is often applied to book media such as text and two-dimensional images only. In this case, it causes learning to be less than optimal so that a learning medium is needed that can help kindergarten students understand the basic characteristics of the shape of the textbook in two dimensions by showing the shape of the object in three dimensions. The purpose of this development is to produce textbook products that have been equipped with Augmented Reality technology in the subject of self for kindergarten class A. The method used in this research is a type of development research known as Research & Development (R&D). The development model used is the Lee & Owens model which has been adapted to the needs of the research. The responses from media experts and material experts received positive responses after the trial. While the product utilization trials were carried out on Class A kindergarten students. And the results obtained overall Augmented Reality Kindergarten thematic teaching book media products on the material of oneself are feasible to use in learning.